THE UNBREAKABLE BOND BETWEEN POET AND DRAFT: ANALYZING ALEXANDER FAYNBERG’S ODE TO DRAFTS - Mirag'zamova Oysha Mirsherzod qizi (TADQIQOTLAR, 2025)
Abstract: This research paper explores Ode to Drafts (Qoralamalar Qasidasi) by Alexander  Faynberg,  a  thought-provoking  poem  that  delves  into  the  intimate relationship  between  a  poet  and  their  drafts.  Through  an  in-depth  analysis  of Faynberg’s  use  of  symbolism,  repetition,  and  philosophical  reflections,  this  paper uncovers the deeper meaning behind the poet’s reverence for the creative process. The poem portrays drafts as not merely preliminary versions of literary works but as living, breathing entities that embody the poet’s struggles, triumphs, and truths. By closely examining key lines, this study highlights how Faynberg elevates the role of drafts from mere writing exercises to sacred artifacts of artistic and spiritual devotion. The full translated version of the poem is included to provide a comprehensive basis for analysis.